Development of a Large-scale Metabolic Modell Model Description and Preliminary Results - Varga, Mónika (Acta Agraria Kaposváriensis, 2006)
Final goal of this work is the more detailed identification of the metabolic processes in the human or animal cells. The computer models are to be applied to solve practical tasks, e.g. in studying the effect of the drugs and toxins. Recently we have started the identification of a large-scale metabolic model by means of the generic bi-layered net model based simulating software, combined with the multiobjective genetic algorithm. Considering the limited set of available measurements, as well as the ill-defined and uncertain knowledge, the development of the model is based on a continuous consultation with the field experts (Vanderbilt Institute of Integrated Biosystem Research and Education, Vanderbilt University, TN, USA). Present work reports about the first steps and the present state of the development of a simulation model on the basis of a published data set.
Keywords: metabolic processes; identification; generic simulator; genetic algorithm